Political economy of privatisation: Poland in comparative perspective - Jan Winiecki (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1991)
Regardless of one's stand on the privatisation issue, there is certainly one point on which all protagonists and antagonists of privatisation agree. This is the political importance of the issue in question. Privatisation part of the transition to the market system is a major political, nor only economic change. Therefore, it should be analysed not only in economic but also in political terms. Politics, or, more precisely, political economy of privatisation is, then, a legitimate - and highly relevant - topic of analysis. Preferences and interests of various actors (public and private ones), ways of articulating these preferences and interests, actors' interaction with the political system, etc., all impinge upon privatisation process and outcomes. Also, the political environment within which the transition has been taking place is of great significance to privatisation. Finally, since transition away from the centrally planned, Soviet-type economy is without precedent, any expectations with respect to both process and outcomes have to be based upon privatisation experience elsewhere. It is this experience that the present writer will look into, first in order to form preliminary expectations about the political economy of privatisation in Poland. First section deals, then, with political economy of privatisation in post-Soviet-type economies (post-STEs for short) in comparison with that in developing countries (LDCs for short).
Keywords: 330; Privatisierung; Polen; Osteuropa; Entwicklungsländer